Exploring fascia in myofascial pain syndrome: an integrative model of mechanisms - Gromakovskis, Vlodeks (Frontiers in Pain Research, 2025)
Myofascial pain syndrome (MPS) is a leading cause of chronic musculoskeletal pain, yet its mechanisms remain debated. Traditional models emphasized muscle contracture or central sensitization, but growing evidence highlights fascia as a biologically active, pain-relevant tissue. Pathological alterations such as densification, fibrosis, and inflammation may generate nociceptive input and sustain persistent symptoms. To explore this perspective, we conducted a conceptual narrative review of studies published between 2000 and 2025 in PubMed, Embase, Scopus, and Google Scholar. Eligible publications included anatomical, histological, imaging, biomechanical, and clinical investigations, and evidence was synthesized narratively into an integrative model of mechanisms. This mini-review followed the SANRA guidelines for narrative reviews. The literature demonstrates that fascia is richly innervated by nociceptors and sympathetic fibers and undergoes pathological changes in patients with MPS. Imaging and histological studies confirm fibrosis, densification, and inflammatory activity in symptomatic fascia. Mechanistic pathways linking fascia to pain include impaired sliding, abnormal mechanotransduction, and neuroinflammatory sensitization. Clinically, patients exhibit tenderness on fascial palpation, imaging evidence of stiffness, and symptomatic improvement after fascia-focused therapies. These findings suggest that fascia functions as a key peripheral driver in MPS. This concept was first formalized as the ‘integrated hypothesis’ by Simons in 2004. Integrating fascia into existing frameworks reconciles muscle-based and central sensitization models, providing a plausible substrate that initiates nociceptive signaling, perpetuates central adaptations, and interacts with psychosocial influences. This integrative model may explain the heterogeneity of MPS and supports multimodal treatment strategies that combine fascial therapies with central and psychosocial interventions. Although current evidence remains preliminary and heterogeneous, recognizing fascia as a central but interconnected contributor to MPS offers a more comprehensive understanding of this syndrome and a clinically relevant framework for future diagnostic and therapeutic innovation in pain medicine.